PKM Pendampingan Usaha Mikro Industri Kripik Pisang dan Singkong di Desa Cikeusal Kecamatan Cikeusal Kabupaten Serang - Surachman Surachman; Mohammad Irhamsyah; Aan Anshori; Ahmad Fajar; M.Adi Husaeni (Batara Wisnu : Indonesian Journal of Community Services, 2022)
The existence of Micro, Small and Medium Enterprises (MSMEs) is very crucial, because it is able to support the needs of family life and to strengthen the national economy. However, it is very unfortunate that after the passing of the Covid-19 pandemic, partner income has decreased quite significantly. Partner problems will try to be overcome through an approach with intensive counseling (mentoring) that is able to train partner soft skills and hard skills through science and technology transfers consisting of Good Manufacturing Practice (GMP) training, food safety counseling, strengthening Business management, improving product packaging and providing supporting production facilities, partners have benefited in these activities. The team consisting of Field Assistant Lecturers (DPL) and students who carry out KKM have carried out this activity well, with the outputs that have been achieved are the publication of activities in the form of videos (youtube), publications in online mass media, improvement of partner production facilities, implementation of bimtek, for partners and scientific articles community service activities and the need for continuous partner assistance